Elucidating isotopic effects in intense ultrafast laser-driven D2H+ fragmentation - Sayler, A. M.; McKenna, J.; Gaire, B.; Kling, Nora G.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, Itzik (My University, 2014)
The triatomic hydrogen molecular ion is instrumental as a benchmark toward understanding the strong-field dynamics of polyatomic molecules. Using a crossed-beams coincidence three-dimensional momentum imaging method, we demonstrate clear isotopic effects in the fragmentation of D[subscript 2]H[superscript +] induced by 7 fs (40 fs), 790 nm laser pulses at an intensity of 10[superscript 16] W/cm² (5×10[superscript 15] W/cm²). Our experiment uniquely separates all fragmentation channels and provides kinematically complete information for the nuclear fragments. For example, we show that for dissociative ionization of D[subscript 2]H[superscript +] there is a large difference in branching ratios of the two-body channels, namely, H[superscript +]+D[superscript +][subscript 2] dominates D[superscript +]+HD[superscript +], whereas there is minimal difference in branching ratios between the dissociation channels H[superscript +]+D[subscript 2] and D[superscript +]+HD.
Keywords: Strong-field dynamics; Polyatomic molecules; Isotopic effects